Purchase of Unit Linked Life Insurance Policies: The Role of Agents’ Relationship-Selling Behavior - Basri, Savitha; Shetty, Ankitha (Indian Journal of Marketing, 2023)
Purpose : The objective of this study was to understand the influence of relationship-selling behavior on the selection of life insurance products. Methodology : Quantitative data were collected from 542 life insurance policyholders in Karnataka by adopting a cross-sectional survey methodology. Findings : Multinomial logistic regression model estimated the channel of distribution (individual agents), trust, interaction intensity, information sharing, and income to influence the selection of life insurance products. Practical Implications : Insurance companies should revamp corporate culture that stresses the interests of the customers over that of agents and curtail adaptive sales practices of agents who sell complex products that do not cover customers’ insurance needs. The promotion of customer-oriented ethical sales behavior focusing on trust, information sharing, and higher interaction intensity is the need of the hour. Efforts should be made to counter systemic short-termism and educate customers on the necessity for long-term investments instead of surrendering the policy where they lose the entire investment. Given that the quality and frequency of insurance agent–customer interactions play a major role in investor decision-making, agents are expected to be responsive and offer personalized inputs to facilitate the purchasing process. Originality : The current study added to the body of evidence supporting the relevance of relationship-selling behavior in the context of ULIPs. It also demonstrated the advantages of the corporate agent (bancassurance) model in not marketing complex products such as ULIPs.